(untitled) (Islas, 2023)
Introduction: We propose a linguistic analysis of the Histoire naturelle des Indes, an anonymous manuscript that presents the fauna, flora, as well as colonial and indigenous life in the Caribbean Basin at the end of the 16th century. Although written in French, the document shows numerous Hispanisms. Methods: We will apply methods of Contact Linguistics, such as etymological, lexical and phonetic-phonological analysis, to the Hispanisms of the manuscript, in order to reconstruct the state of evolution of the Spanish spoken at that time in that area. Results: We will show that some lexical uses that today characterize the Spanish spoken in Venezuela, Colombia and the Antilles are already present in the French manuscript, long before they manifest themselves in the Spanish documentation. In addition, the kind of Spanish that the authors heard around them had a southern (Andalusian) imprint. Conclusions: Taken together, the analysis illustrates the importance of considering the Caribbean as a contact zone. Any attempt to understand or reconstruct the history of Caribbean Spanish must necessarily take into account the other languages that have coexisted with it in the multilingual space of the Caribbean basin.